The Effect of Online Learning on the Results of Hair Coloring Practices in 11th Grade Vocational High School Students (SMK) During the Covid-19 Pandemic - Mimi Yupelmi (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
The implementation of learning in hair coloring subjects which have problems with the lack of equipment and cosmetic materials becomes a barrier to achieving learning objectives which results in decreased results of students' hair coloring practices. The purpose of this study was to analyze and determine the effect of online learning on the results of the Xi class student hair coloring practice at SMK N 7 Padang during the Covid-19 pandemic. The population of this study was students of SMK N 7 Padang, while the sample was all students of class XI, totaling 102 people. The instrument used in this study was a questionnaire arranged on a Likert scale. Questionnaires were given to students for a limited class of 30 people to obtain trial data which would be analyzed for validity and reliability. The sampling technique used was total sampling by making all students of class XI as the sample data. Based on the research results, it was found that the relationship between online learning variables as the independent variable and the results of hair coloring was the dependent variable